Formation Pathways toward 2‐ and 4‐Methylbenzaldehyde via Sequential Reactions from Acetaldehyde over Hydroxyapatite Catalyst. Issue 11 (28th April 2017) - Moteki, Takahiko; Rowley, Andrew T.; Bregante, Daniel T.; Flaherty, David W.
Abstract: Condensation reactions of biomass derived C2 and C4 aldehydes form both ortho ‐ and para ‐tolualdehydes (2‐MB and 4‐MB, respectively). The complete reaction network and the detailed mechanisms, however, have not been fully described. Here, analysis of the products formed by sequential condensation reactions of acetaldehyde and 2‐butenal suggests that 2‐ and 4‐MB products form via aromatization of 2, 4, 6‐octatrienal and of highly reactive acyclic intermediate(s) formed via self‐addition of 2‐butenal, respectively. The exact positions at which C−C bonds form between C4 co‐reactants to create 4‐MB products were investigated by using reactant mixtures containing combinations of 2‐butenal, 2‐butenol, and 3‐methyl‐2‐butenal as model reactants. The last two reactants can form products that may be assigned to specific reaction pathways (not distinguishable during self‐addition of 2‐butenal) and also have decreased reactivity at specific carbon atoms. The analysis of the products suggests that 4‐MB species form via 2‐butenal self‐addition by nucleophilic attack of the α‐C to the carbonyl‐C. Additionally, Diels–Alder reactions (between C6 and C2 intermediates) do not contribute in any significant manner to the formation of 4‐MB. These findings complete the description of the reaction network that forms 2‐ and 4‐MB from acetaldehyde on hydroxyapatite. Abstract : Competing pathways form isomers : The 2‐ and 4‐methylbenzaldehydes are formed by hydroxyapatite‐catalyzed condensation and/or addition reactions of bio‐derived small aldehydes. By analyzing the products formed by self‐ and cross‐condensation of the mixture of C2 and C4 reactants, the overall picture of the reaction network and the most plausible parallel reaction pathways are proposed.